The Use of Animated Videos in Increasing the Arabic Learning Interest - Ade Arip Ardiansyah; Nanang Kosim; Acep Hermawan (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2022)
Interest in learning has an essential role in learning process. If the interest in learning is low, it can affect student learning success. This study aims to determine the effectiveness of animated videos as a medium in increasing student interest in learning Arabic. This study used a descriptive qualitative method with data collection techniques in observations, interviews, questionnaires, and documentation. The results of this study indicate that the use of animated videos can increase student interest in learning Arabic. The use of animated videos in Arabic learning can increase student enthusiasm and motivation, facilitate students to learn and memorize easily, and help teachers to present material easily. Meanwhile, the inhibiting factors are the student limited network connection and internet quota. Moreover, not all teaching materials can be presented in animated videos, and also teachers skills in making and teaching Arabic using animated videos are insufficient